Associations of sleep characteristics with alpha‐synuclein in cerebrospinal fluid in older adults - Xiao‐Tong Wang; Feng‐Tao Liu; Yan‐Lin Bi; Xue‐Ning Shen; Wei Xu; Jian Wang; Lan Tan; Jin‐Tai Yu (Annals of Clinical and Translational Neurology, 2020)
Abstract Objective Sleep disorders as a preclinical symptom of synucleinopathies become more prevalent in older adults. Synucleinopathies might be caused by the abnormal aggregation of alpha‐synuclein in the brain, which was indicated by alpha‐synuclein levels in cerebrospinal fluid (CSF). We aimed to investigate associations of sleep characteristics with CSF alpha‐synuclein in older adults. Methods Our study recruited 536 cognitively intact individuals (aged between 40 and 90 years old) from the Chinese Alzheimer’s Biomarker and Lifestyle study. Sleep behaviors were assessed by Pittsburgh Sleep Quality Index and total alpha‐synuclein in CSF was measured by enzyme‐linked immune‐sorbent assay. We used multiple linear and non‐linear regression models for research. Results Significant non‐linear associations of CSF alpha‐synuclein with sleep time and duration were revealed. Individuals who went to bed and fell asleep too early or late tended to have lower CSF alpha‐synuclein (reflection point for time to bed and fall asleep were 10:26 p.m. and 10:40 p.m.). Lower CSF alpha‐synuclein was also observed in individuals with either excessive or insufficient sleep duration (reflection point: 7.24 hours). Besides, overall poor sleep quality (β = −0.0621; P = 0.0242), longer sleep latency (β = −0.0415; P = 0.0174) and lower sleep efficiency (β = 0.0036; P = 0.0017) showed linear associations with lower CSF alpha‐synuclein. Sleep disturbances and daytime dysfunction were not significantly associated with CSF alpha‐synuclein. Interpretation Poor sleep was associated with lower levels of CSF alpha‐synuclein in older adults, which may provide new insight into the prevention of synucleinopathies.